Placoneis cocquytiae, a new raphid diatom (Bacillariophyceae) from the Senegal River (Senegal, West Africa) - Fofana, Cheikh Abdoul Kader; Sow, El Hadji; Taylor, Jonathan; Ector, Luc; de Vijver, Bart Van (Phytotaxa, 2014)
During a survey of the freshwater diatom flora of the Senegal River, an unknown Placoneis species was observed that was initially identified as Placoneis gastrum. Detailed morphological analysis using both light and scanning electron microscopy observations revealed sufficient morphological differences to separate this species as Placoneis cocquytiae sp. nov. The new species is characterized by a rather broadly lanceolate to elliptic-lanceolate valve outline with rostrate, protracted, broadly rounded apices. The central area has an irregular shape due to the shortening of several striae. An isolated pore is lacking. The new species is compared with similar Placoneis and Navicula s.l. taxa and a short biogeographical analysis based on confirmed African records is presented. So far, P. cocquytiae is also present in Zambia and Lake Tanganyika.